2018
DOI: 10.1250/ast.39.234
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of temporal cue on the perception of speaker individuality and vocal emotion for noise-vocoded speech

Abstract: This paper investigates the importance of temporal cues in the perception of speaker individuality and vocal emotion. Experiments of speaker and vocal-emotion recognition were carried out using an analysis/synthesis method of noise-vocoded speech (NVS). The temporal resolution of NVS was controlled by varying the upper limit of modulation frequency (0, 0.5,1,2,4,8,16, 32, and 64 Hz). In addition, the role of temporal cue in the different spectral resolution condition was also investigated by varying the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…In our previous study, in order to study the contribution of temporal modulation cues on vocal-emotion recognition, we varied the spectral and temporal resolution of noisevocoded speech stimuli presented to normal hearing listeners. The detailed method of signal processing to generate noise-vocoded speech can be found in [11]. The Fujitsu Japanese Emotional Speech Database was used.…”
Section: Perceptual Data Of Vocal-emotion Recognition Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, in order to study the contribution of temporal modulation cues on vocal-emotion recognition, we varied the spectral and temporal resolution of noisevocoded speech stimuli presented to normal hearing listeners. The detailed method of signal processing to generate noise-vocoded speech can be found in [11]. The Fujitsu Japanese Emotional Speech Database was used.…”
Section: Perceptual Data Of Vocal-emotion Recognition Experimentsmentioning
confidence: 99%
“…In our previous study, we investigated the contribution of temporal modulation cues on the perception of nonlinguistic information using noise-vocoded speech [11]. The results showed that the temporal modulation cues play an important role in the perception of vocal emotion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations